Părintele Profesor Liviu Galaction Munteanu: Popasuri pastorale reflectate în opera sa - Greabu, Lucian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
One of the great personalities of the theological school in Romania is that of Father Professor Liviu Galaction Munteanu. His theological training, which began in Sibiu, was completed at the prestigious Faculty of Theology in Cernăuţi, where he obtained a doctorate in the New Testament discipline. Most of his work was published in the magazine Renaissance, in the column „foileton”, and then saw the light of the press as studies or volumes. Other writings were published in the magazine Illustrated Life, so that durig his journalistic intinerary, he made an important contribution to the development of the theological heritage in Romania. His work, which covers a rich thematic palette, reflects an exceptional theological preparation that was used in order to carry out the pastoral mission. We live in a culturally emancipated society, in which some consider religious truths obsolete or manifest opposition to them. In these conditions, an active pastoral care is needed from the priests, and Father Liviu G. Munteanu remains, from this perspective, a paradigm.